2021
DOI: 10.1016/j.jsams.2020.11.016
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity, mental health and well-being of adults during initial COVID-19 containment strategies: A multi-country cross-sectional analysis

Abstract: Objectives To assess physical activity (PA), mental health and well-being of adults in the UK, Ireland, New Zealand and Australia during the initial stages of National governments’ Coronavirus disease (COVID-19) containment responses. Design Observational, cross-sectional. Methods An online survey was disseminated to adults (n = 8,425; 44.5 ± 14.8y) residing in the UK, Ireland, New Zealand and Australia within the first 2-6 weeks of governmen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

38
242
6
15

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 202 publications
(301 citation statements)
references
References 25 publications
38
242
6
15
Order By: Relevance
“…This is in line with other research that has shown the benefits of physical activity on mental health [18,[43][44][45] and in particular with a survey conducted in New Zealand that showed positive correlations between self-reported PA and well-being [43]. In this study, people who had negative or no change in their PA from pre-during lockdown, reported worse well-being, depression, stress and anxiety compared to those who had positive changes in PA [43]. During lockdown in Canada, men and women who were surveyed, reported very good or excellent mental and physical health if they were exercising outdoors and if they reduced their screen time [14].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This is in line with other research that has shown the benefits of physical activity on mental health [18,[43][44][45] and in particular with a survey conducted in New Zealand that showed positive correlations between self-reported PA and well-being [43]. In this study, people who had negative or no change in their PA from pre-during lockdown, reported worse well-being, depression, stress and anxiety compared to those who had positive changes in PA [43]. During lockdown in Canada, men and women who were surveyed, reported very good or excellent mental and physical health if they were exercising outdoors and if they reduced their screen time [14].…”
Section: Discussionsupporting
confidence: 92%
“…In our survey, those respondents who continued to maintain their usual level of physical activity throughout the lockdown, recognized the importance of PA on their well-being especially mental health. This is in line with other research that has shown the benefits of physical activity on mental health [18,[43][44][45] and in particular with a survey conducted in New Zealand that showed positive correlations between self-reported PA and well-being [43]. In this study, people who had negative or no change in their PA from pre-during lockdown, reported worse well-being, depression, stress and anxiety compared to those who had positive changes in PA [43].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The perceived impact of COVID-19 on training alongside subsequent reductions in training frequency comparative to pre-COVID-19, at both T1 and T2, indicate notable disruptions in the ability of strength athletes' to train effectively during the pandemic. This is concerning, as several studies in the early COVID-19 stages have shown that a reduction in physical activity has a negative impact on mental health and well-being ( 78 , 79 ). Our findings likewise showed the perceived impact of the pandemic on their training was negatively linked with aspects of their psychological health at T1.…”
Section: Discussionmentioning
confidence: 99%
“…Even light physical exercise could help relieve some of the negative psychological health impacts among isolated older adults due to COVID-19 [ 65 , 66 ]. To promote physical activity, public health initiatives should target particular populations (e.g., men and young adults) that are more vulnerable to the harmful impacts of physical distance and/or self-isolation [ 67 ].…”
Section: Discussionmentioning
confidence: 99%